2022
DOI: 10.3390/nu14040848
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Convenience Cooking Product Use and Vegetable Intake

Abstract: Australians’ vegetable intakes are low, and strategies are needed for improvement. Popular convenience cooking products (meal bases and recipe bases, ready-made marinades, and convenience cooking sauces) address common cooking and vegetable consumption barriers (cost, time, and cooking skills). However, relationships between their usage and vegetable intakes have not been established. Therefore, Australian adults were surveyed on convenience cooking product use, vegetable intake and variety, behaviours when ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This study is the first to investigate the relationship between the frequency of convenience cooking product use and outcomes related to cooking confidence, cooking creativity and vegetable intakes. These findings extend upon previous research studying users of these products, compared to non-users, without consideration of the frequency of use [ 25 ]. The findings here regarding cooking creativity and confidence complement the earlier findings that found use was linked to higher cooking confidence and creativity, with more regular use of convenience cooking products (meal/recipe bases, simmer sauces and pasta sauces) being associated with higher scores.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study is the first to investigate the relationship between the frequency of convenience cooking product use and outcomes related to cooking confidence, cooking creativity and vegetable intakes. These findings extend upon previous research studying users of these products, compared to non-users, without consideration of the frequency of use [ 25 ]. The findings here regarding cooking creativity and confidence complement the earlier findings that found use was linked to higher cooking confidence and creativity, with more regular use of convenience cooking products (meal/recipe bases, simmer sauces and pasta sauces) being associated with higher scores.…”
Section: Discussionsupporting
confidence: 83%
“…The findings here regarding cooking creativity and confidence complement the earlier findings that found use was linked to higher cooking confidence and creativity, with more regular use of convenience cooking products (meal/recipe bases, simmer sauces and pasta sauces) being associated with higher scores. Here, the frequency of use correlated with vegetable variety scores, with more frequent use linked to higher variety, which is interesting given there was no difference in variety scores between users and non-users previously [ 25 ]. However, this did not result in a higher overall vegetable consumption level.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The addition of this information to food packaging has been shown to help improve intakes because consumers have been found to generally follow back of package recommendations. 16,17 Nutrient fortified sauces and condiments, such as yeast extract spreads, may also be an important source of key nutrients, as indicated by the current analysis. However, there is a need to work with food manufacturers regarding product reformulation such that the overall nutrient profiles are improved.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, through convenience sampling, we showed that those who report using convenience cooking products have cooking confidence and cooking creativity, (3) and also typically have lower vegetable intakes. (4) This study presents a representative sample of Australian who were self-reported consumers of convenience cooking and assesses how cooking confidence and creativity and markers of vegetable intake relate to frequency of use. A demographically balanced panel of Australian adults were surveyed ( n = 1034; Qualtrics panel) on their frequency of use of convenience cooking products, cooking confidence (7-item scale) and creativity (6-item scale), and their typical vegetable intake (serves/day) and their vegetable variety (14-item scale).…”
mentioning
confidence: 99%